Work Motivation, Work Discipline, and Work Environment: Their Effects on Employee Performance at PT TRAD Indonesia - Imam Sucipto; Ahmad Gunawan; Dadang Heri Kusumah (East Asian Journal of Multidisciplinary Research, 2022)
PT Trad Indonesia is a Japanese company located in Indonesia. The automotive company is located at Jalan Jababeka II, Kavling C-8, Jababeka Industrial Estate, Cikarang, Bekasi 17530, West Java. However, based on the experience gained and observations made by the researchers, there are employee problems, namely production targets that are difficult to achieve. This research was conducted to find out the effects of work motivation, work discipline, and work environment on employee performance at PT Trad Indonesia. The population consisted of 76 workers. Because the number of members of the population is fewer than 100 people, the researchers took all members of the population as a sample. Thus, the sampling technique used in this study is Non-Probability Sampling with a type of saturated sampling. Multiple Linear Regression Analysis is used to analyze data using SPSS version 22 software. According to the results obtained, partially work motivation, work discipline, and work environment positively affect employee performance. Simultaneously, work motivation, work discipline, and work environment also affect employee performance.